96 VITAMIN D CONTENT IN BODY FAT AND THE CONSEQUENCES OF BARIATRIC SURGERY ON VITAMIN D STATUS. (1st March 2005) - Holick, M. F.; Ingersoll, D.; Lu, Z.; Chen, T.; Forse, A.
Abstract : We have previously documented that obesity is associated with vitamin D deficiency because whether coming from sun exposure or diet the vitamin D bioavailability is reduced by more than 50% in obese compared to non-obese adults. It has been assumed that vitamin D being fat-soluble was being sequestered in body fat. However to date there has been no report of the isolation of vitamin D from human body fat. We recruited 10 morbidly obese adults who were schedule for bariatric surgery. After obtaining informed consent and at the time of surgery we obtained abdominal fat. The abdominal fat was extracted for its lipid content and then saponified. It was prepurified on a straight phase Sep pak column followed by reverse phase and straight phase high performance liquid chromatography. Blood was collected before the surgery and at 3-month intervals after the surgery. The vitamin D content in human fat ranged between 4-320 ng of fat. The human fat contained both vitamin D2 and vitamin D3. To determine whether the mobilization of vitamin D from body fat after bariatric surgery could substantially raise blood levels of 25(OH)D we measured circulating concentrations of 25(OH)D at 3-month intervals after the surgery. There was no significant change in circulating concentrations of 25(OH)D in subjects that blood was collected from 3 and 6 months after the surgery. These results provide evidence that body fat sequesters vitamin D and this is the likely explanation for why obesity is associated with vitamin D deficiency. Furthermore, the mobilization of body fat after bariatric surgery has little effect on vitamin D status suggesting that as the fat is being mobilized that the vitamin D is being metabolized and excreted.